1984
DOI: 10.1159/000260742
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Urea and Human Enamel

Abstract: In this paper the interaction of urea on plaque-free sound human enamel is described. In 1 week urea penetrates in the enamel several hundred micrometers. It weakens or destroys part of the peptide structure, especially interprismatically. Urea does not or not measurably attack the organic matrix between the crystallites. Due to the urea interaction organic material normally plugging natural defects in the enamel surface, especially in the perikymata, is removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 0 publications
1
38
0
3
Order By: Relevance
“…It has been reported that urea, which breaks down to carbon dioxide and ammonia, may affect the interprismatic regions of enamel. [48][49] Urea could denature the protein structure and might cause structural and morphological alterations of enamel through the degradation of organic molecules, such as amelogenin. 28 On the other hand, since urea is alkaline, it raises the pH of the bleaching products, thus reducing the demineralization potential.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that urea, which breaks down to carbon dioxide and ammonia, may affect the interprismatic regions of enamel. [48][49] Urea could denature the protein structure and might cause structural and morphological alterations of enamel through the degradation of organic molecules, such as amelogenin. 28 On the other hand, since urea is alkaline, it raises the pH of the bleaching products, thus reducing the demineralization potential.…”
Section: Discussionmentioning
confidence: 99%
“…Urea is capable of penetrating enamel and affecting the interprismatic region [15]. It is also capable of attacking the protein structure and denatures it.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that urea released by carbamide peroxide has an ability to penetrate enamel and affect not only the surface, but also the interprismatic regions of enamel 28) . On a further note about the effect of urea, it has been reported that the presence of urea in bleaching agents contributed to various surface morphological changes in enamel 29) .…”
Section: Discussionmentioning
confidence: 99%